Effect of Teachers’ Mathematical Knowledge for Teaching (Mkt) on Mathematical Content Knowledge (Mck) and Mathematics Achievement of Students at Secondary Level - Aslam, Namirah; Siddiquah, Aishah (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to find out the effect of teachers’ Mathematical Knowledge for Teaching (MKT) on the students’ Mathematical Content Knowledge (MCK) and the students’ achievement in mathematics at secondary level. The research was causal comparative. The participants of the study were 100 mathematics teachers and 1500 grade 10th and 11th students randomly selected from 33 secondary and all the 17 higher secondary public schools of district Lahore. Two instruments were developed out of the Study of Instructional Improvement (SII) survey (Hill, Schilling, & Ball, 2008) to measure teachers’ MKT and students’ MCK. A mathematics achievement test was developed by the researchers according to the national curriculum of secondary level. All the three instrument were validated from experts and pilot tested. Descriptive statistics, correlation and ANOVA were applied on the data. The result showed that there was a significantly positive relationship between teachers’ MKT and students’ MCK and between students’ MCK and students’ achievement in mathematics. However, no significant relationship was found between teachers’ MKT and students’ achievement in mathematics. Further analysis of demographic variables revealed that another variable “help in study at home” is affecting the MCK and achievement of students as an intervening variable.